Case report: A case of delayed cutaneous metastases from signet-ring cell mixed-type gastric cancer - Yao, Shaohua; Zhou, Peng; Li, Yiqing; Li, Qin (Frontiers in Oncology, 2023)
Background Signet-ring cell gastric carcinoma is a highly malignant tumor, with the characteristics of strong invasiveness, rapid progression, a high degree of malignancy, and generally poor prognosis. The most common site of metastases is the abdominal organs, especially the liver, while delayed cutaneous metastases are rare. Case presentation We report a case of cutaneous metastases on the head, groin, and thigh, which recurred 7 years after signet-ring cell gastric carcinoma surgery. The patient was diagnosed with a 2.0×1.5×1.0cm tumor at the angle of stomach, and treated with Billroth II distal gastrectomy accompanied with D2 lymph node dissection. According the pathology, the stage was pT1N3M0. Then the patient received two cycles of oxaliplatin and tegafur chemotherapy, which was discontinued due to the inability to tolerate the side effects of chemotherapy. Seven years after the surgery, the patient initially presented with a fleshy mass on the head and beaded nodules in the groin; then, the mass gradually became larger, along with the thighs turning red, swollen, and crusty. Firstly, the patient was diagnosed with “lower extremity lymphangitis” and treated mostly with anti-inflammatory, promote lymphatic return, detumescence and elastic force cannula in vascular surgery department. However, the symptoms relieved insufficient. Finally, the skin biopsy indicates a signet-ring cell gastric carcinoma cutaneous metastasis. The whole-body PET-CT examination showed multiple nodules with increased metabolism. Then the patient was transferred to The Department of Oncology for further chemotherapy. Conclusion Our case highlights that gastric tumor recurrence and metastasis should be highly suspected when skin lesions appear in patients with signet-ring cell gastric carcinoma. At the same time, multidisciplinary consultation and close cooperation between surgeons, oncologists, and dermatologists are of great significance to the diagnosis and treatment of this disease.